THE CLASSIFICATION OF PARONYMS IN THE RUSSIAN AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2023)
The article deals with the classification of paronyms in both Russian and Uzbek languages, where the division occurs according to morphological and lexical-semantic features. The phonological and word-formation features of paronyms in the studied languages ​​are revealed, their similar and different linguistic features are revealed. In the course of the story, a number of serious and reasonable conclusions are given, supported by examples from scientific and fiction literature.